The Implementation of Economic Border Policing to Enhance Inclusive Economic Productivity - Pratama, Bellen Anggara (International Journal of Law Dynamics Review, 2023)
Sustainable and inclusive development is the fundamental objective in reaching national development goals. National Medium-Term Development Plan (RPJMN) 2020-2024 aims to enhance Indonesia's per capita income to that of upper-middle-income countries (MIC) with enhanced infrastructure, human resources, public services, and citizen welfare. This RPJMN objective aligns with the Sustainable Development Goals (SDGs), which comprise 17 interrelated goals and indicators grouped into sevent development agendas. Implementation of the SDGs on a regional level is vital to attaining these objectives, as regional policies and development programmes can make a substantial contribution. The SDGs underline the significance of achieving inclusive and sustainable economic growth, universal access to basic services, natural resource management, and strengthening local institutions. In order to attain elevated economic growth, Indonesia necessitates an economic metamorphosis through the augmentation of productivity across several sectors. The 2023 Policy Plan (RKP 2023) adopts the theme "Increasing Productivity for Inclusive and Sustainable Economic Transformation," in order to reinforce economic resilience, enhance regional development and advance human resource quality. In this context, Economic Border Policing emerges as an important strategy for supporting the revival of the national economy through cooperatives and micro, small, and medium-sized enterprises (MSMEs) in border regions. Economic Border Policing is multifaceted, encompassing illegal trade control, trade and investment monitoring, welfare and rights protection, and the promotion of local economic development in border regions. Implementing Economic Border Policing is expected to create a safe and effective environment for inclusive and sustainable economic growth in border areas, facilitating enhanced economic productivity and comprehensive regional development.